The Effect of Applying Blended Learning Strategies Flipped Classroom Model on Students’ Critical Thinking Skills - Zulhamdi Zulhamdi; Hafnati Rahmatan; Wiwit Artika; Andi Ulfa Tenri Pada; Ismul Huda (Postgraduate, University of Mataram, 2022)
Critical thinking skills are competencies that are expected to be possessed by every student in 21st century learning. One of the efforts that can be made to improve students' critical thinking skills is to apply the flipped classroom learning model. This study aims to determine the effect of students' critical thinking skills through the application of the blended learning model of the flipped classroom. The research approach used is quantitative with a quasi-experimental type of research, the research design used is pretest-posttest non-equivalent control group design. Sampling used a total sampling technique from the entire population of 102 students of class XI IPA at SMAN 1 Peulimbang. The instrument used to measure critical thinking skills is in the form of essay questions accompanied by an assessment rubric. Data on critical thinking skills were analyzed by parametric statistics using the independent sample t test. The results showed that the value of < 0.05, then there was an effect of students' critical thinking skills after the application of the blended learning model of the flipped classroom on the respiratory system material